1955
DOI: 10.1021/j150525a016
|View full text |Cite
|
Sign up to set email alerts
|

The System Sodium Sulfate–Sodium Molybdate–Water

Abstract: Solubility relationships in the system sodium sulfate-sodium molybdate-water at various temperatures are reported. At temperatures where it exists as a stable phase, the decahydrate of each of these salts takes up the other in solid solution, but the amount of sodium sulfate taken up by sodium molybdate decahydrate is very small. Boundary conditions for some of the three-phase equilibria in the system have been determined, as have the locations of two quadruple points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Both compounds are highly soluble in water, crystallizing at room temperature as orthorhombic dihydrates (space group Pbca, Atovmyan & D'yachenko, 1969;Farrugia, 2007). Below 283.5 K for the molybdate and 279.2 K for the tungstate, crystals grow with ten water molecules per formula unit (Funk, 1900;Cadbury, 1955;Zhilova et al, 2008). The high solubility in water and propensity towards forming hydrogen-bonded hydrates (unlike the heavier alkali metal molybdates and tungstates) suggests that both compounds would be excellent candidates for formation of hydrogen-bonded complexes with water soluble organics, such as amino acids, producing metalorganic crystals with potentially useful optical properties (cf., glycine lithium molybdate; Fleck et al, 2006).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Both compounds are highly soluble in water, crystallizing at room temperature as orthorhombic dihydrates (space group Pbca, Atovmyan & D'yachenko, 1969;Farrugia, 2007). Below 283.5 K for the molybdate and 279.2 K for the tungstate, crystals grow with ten water molecules per formula unit (Funk, 1900;Cadbury, 1955;Zhilova et al, 2008). The high solubility in water and propensity towards forming hydrogen-bonded hydrates (unlike the heavier alkali metal molybdates and tungstates) suggests that both compounds would be excellent candidates for formation of hydrogen-bonded complexes with water soluble organics, such as amino acids, producing metalorganic crystals with potentially useful optical properties (cf., glycine lithium molybdate; Fleck et al, 2006).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The phase diagrams of ternary subsystems of the NaOH–Na 2 MoO 4 –Na 2 SO 4 –H 2 O quaternary system, such as the Na 2 MoO 4 –Na 2 SO 4 –H 2 O system and the NaOH–Na 2 SO 4 –H 2 O system, , have been previously studied. However, the phase diagram of the NaOH–Na 2 MoO 4 –Na 2 SO 4 –H 2 O system has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…In the Na 2 SO 4 -H 2 O system, a metastable heptahydrate (Na 2 SO 4 Á7H 2 O) has been known for over a century but was characterized in detail only very recently (Oswald et al, 2008;Hamilton & Menzies, 2010;Derluyn et al, 2011;Saidov et al, 2012), and an octahydrate (Na 2 SO 4 Á8H 2 O) was reported by Oswald et al (2008) as the stable phase formed at 1.54 GPa. Although the Na 2 SeO 4 -H 2 O system is qualitatively identical to the Na 2 SO 4 -H 2 O system (Funk, 1900;Meyer & Aulich, 1928), there are other stable hydration states in the Na 2 CrO 4 , Na 2 MoO 4 and Na 2 WO 4 -H 2 O systems; Na 2 CrO 4 Á10H 2 O melts incongruently to a hexahydrate at 292.675 K and then to a tetrahydrate at 299.05 K (Richards & Kelley, 1911), whilst both Na 2 MoO 4 Á10H 2 O and Na 2 WO 4 Á10H 2 O melt incongruently to a dihydrate, at 283.43 and 279 K, respectively (Funk, 1900;Cadbury, 1955;Zhilova et al, 2008). Extensive substitution of sulfate into these alternative hydrates has been reported (Richards & Meldrum, 1921;Cadbury et al, 1941;Cadbury, 1945).…”
Section: Introductionmentioning
confidence: 99%